2020
DOI: 10.1002/tesq.584
|View full text |Cite
|
Sign up to set email alerts
|

“English‐Only Is Not the Way to Go”: Teachers’ Perceptions of Plurilingual Instruction in an English Program at a Canadian University

Abstract: Although recent calls have been made for a plurilingual shift in language learning, particularly in countries with linguistically and culturally diverse populations, teachers are still unsure about how to apply plurilingualism in the classroom. There remains a paucity of studies investigating the disconnect between the theory and implementation of the plurilingual shift. This quasi‐experimental study addressed these challenges by implementing plurilingual instruction in one English language program in a Canadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 54 publications
(83 reference statements)
2
27
0
2
Order By: Relevance
“…From a pedagogical perspective, the results of the study are important as they show that even in classes where only one target language (English) is the focus, plurilingual instruction can be effectively infused into the curriculum. While the results of this study are solely based on students' voices, the participating teachers unanimously reported a preference for plurilingual instruction compared with monolingual instruction (Galante et al 2020). The plurilingual instruction in this study was delivered in the form of weekly language tasks that suited the needs of the EAP program and this decision was made in collaboration with the program director and the teachers to avoid major disruptions (Galante et al 2019).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…From a pedagogical perspective, the results of the study are important as they show that even in classes where only one target language (English) is the focus, plurilingual instruction can be effectively infused into the curriculum. While the results of this study are solely based on students' voices, the participating teachers unanimously reported a preference for plurilingual instruction compared with monolingual instruction (Galante et al 2020). The plurilingual instruction in this study was delivered in the form of weekly language tasks that suited the needs of the EAP program and this decision was made in collaboration with the program director and the teachers to avoid major disruptions (Galante et al 2019).…”
Section: Discussionmentioning
confidence: 81%
“…The study This was a mixed-methods study that included a quasi-experimental component with treatment and comparison groups in intact Academic Listening and Speaking (ALS) classrooms of an EAP program in Toronto, Canada. As part of a larger investigation of the implementation of plurilingual instruction (Galante et al 2019) and teachers' perceptions (Galante et al 2020), the study reported in this article focuses on data gathered from students only.…”
Section: Methodsmentioning
confidence: 99%
“…En cuanto a las estrategias de translenguaje aplicadas, Celic y Seltzer (2016, p. 2) expresan que las tablas de cognados son herramientas útiles para los bilingües emergentes porque estas palabras ilustran las conexiones lingüísticas a través de diferentes lenguas. Sobre las comparaciones gramaticales, Galante et al, (2020) explican que "los estudiantes pueden reflectar sobre si existe la misma forma gramatical en sus lenguas y lo similar o diferente que es" (p.983). Asimismo, Celic y Seltzer (2016, p. 5) afirman que es importante hacer que los alumnos sean conscientes de cómo la sintaxis es similar o diferente a la de su lengua materna para que el uso de la lengua meta pueda ser más transparente.…”
Section: Discussionunclassified
“…Implications on embedding plurilingualism and plurilculturism can be expected at higher learning institution syllabus content and learning direction. Learners who feel inferior and intimidated by the language would be able to feel more at ease in learning the second language when the content is more familiar and relatable to them (Galante, 2020) After all, among the main objectives of CEFR is to support plurilingualism and diversification of learners by focusing on the quality and transparency based on learners' need, interest and age (CoE, 2018).…”
Section: Conclusion and Implicationmentioning
confidence: 99%